VERSATILE IN COMBINATION; TRAMADOL AND BUPIVACAINE, AS CAUDAL BLOCKANALGESIA FOR PEDIATRIC INFRA-UMBILICAL SURGERIES - Naila Zahoor Awan et al (Baqai Journal of Health Sciences)
Objective: To determine the effect of analgesia postoperatively when bupivacaine is used alone and in combination with tramadol as caudal block anesthesia in pediatric infra-umbilical surgeries Subject and Methods: A study conducted in Pediatric Surgery Department of Civil Hospital Karachi, Dow University of Health Sciences. This is a Randomized trial which includes a total of 60 children undergoing infra-umbilical surgeries. Patients got randomly allocated into 2 groups, 30 in (Bupivacaine-Tramadol) group A, which were given 0.5ml/kg 0.25% bupivacaine & 1mg/kg tramadol while 30 patients in group Bwho received 0.5ml/kg 0.25% bupivacaine as caudal block anesthesia respectively. Hemodynamic status was monitored. The end point of the study was onset of pain in patient if Baker-Wong FACES Pain Rating Scale Score >4. The time frame of our study was six months from 1st July – 31st December 2015. Results: The mean age was 4.66±1.79 years. Mean duration of postoperative analgesia was significantly prolonged in group A as compared to group B (p =0.0005). Conclusion: Tramadol when added with bupivacaine in caudal analgesic block has an additive and long-lasting effect and there was a decreased need to provide rescue analgesia after surgery